IMPLEMENTASI NILAI-NILAI PANCASILA DALAM MATA PELAJARAN PPKn DAN IMPLIKASINYA TERHADAP PEMBINAAN KARAKTER SISWA KELAS 4 SDN CILEGON 4 - Waheda Syifaurrahmah, - (2022)
Pancasila as the state ideology has an important role as the foundation of social and state life. Pancasila is considered as a way of life and a builder of the nation's character. The values contained in Pancasila are very influential in shaping the character and quality of human resources. The values contained in each item of Pancasila contain meanings that reflect the nation. Citizenship education (PPKn) is a social subject that focuses on the formation of citizens who understand and are able to carry out their rights and obligations to become intelligent, characterized, and skilled citizens contained in Pancasila and the 1945 Constitution. During this time, many social changes occurred and many deviant behaviors were found in students in Indonesia such as violations of school rules, violence among friends, skipping school, and so on. These problems will affect the lives of students. If there is no inculcation of Pancasila values, students will continue to fall into these problems. With this case, the school environment is considered very appropriate for inculcating the values of Pancasila. Therefore, schools are the right means for inculcating Pancasila values, because students can learn, and seek experience. The writing of this research uses case study research in collaboration with the teacher and the subject being studied. This research is sourced from the data of the 4th grade students of SDN Cilegon 4, totaling 27 students. in this study using questionnaires by students and resulted in a percentage of 91% answering with the right response and 9% answering with the wrong response. From these results the researchers concluded that the implementation of Pancasila values in Civics subjects and their implications for character building for 4th grade elementary school students in Cilegon 4 had been well achieved.